Associativismo farmacêutico: uma estratégia de mercado das pequenas e médias empresas no Triângulo Mineiro e Alto Paranaíba - Nascimento, Ana Karina Rossi Bertoldo (2014)
The globalisation of the capital na trading prometed a quick strengthening of the big networks active in the Market, making it more and more competitive and exclusionary. Compete with these networks in a balanced way, is a big challenge for the small and big businessmen. With the purpose to establish an equity between the small and the medium companies, in relation to the big networks, new trade techniques are presented, and new strategies are implemented in order to achieve the market and the consumers. It s in this context that appears the associativism between the small and medium companies that seek to strengthen to face the challenges imposed by the growth of the commercial networks. Not differently from other segments, the pharmaceutical commerce also adheres new practices as the associativism, seeking, through the joint action, higher competitiveness. Through this strategy, the networks have the power to negotiate deadlines, purchases and marketing actions, such as, the ones that give higher competitiveness. Aiming to study the changes that have occurred to the pharmaceutical commerce, this work has as the main objective to analyze the main commercial and local strategies used by the associativists netwoks that act in the Triângulo Mineiro Mesoregion and Alto Paranaíba, with an emphasis to the associations that are being formed with the aim to strengthen the small and medium companies that act in the local pharmaceutical branch. The small and medium bisinnessmen face many difficulties, mainly when the competitiveness becomes the differential able to gain the consumers and make them allied to the process of growth and expansion of the market. To adapt to a market more and more demanding, with a new economic and commercial form, imposed by the globalization of the capital, becomes the big challenge for many companies. To face the difficulties, it s necessary to find new and effective strategies that establish combinations such as, the multiples alliances that provide the growth of small and medium companies that act in the same commercial branch, as it is the study aim of this research. The small and medium businessmen face many difficulties such as, qualified labour, the inaccessibility to innovative products due to the high prices, the innovative products due to the high prices, the informal competition, the excessive bureaucracy to get access to credit and even, the lack of experience in administrating his own business. The associativism can be considered a good strategy, since it has provided the companies, overcome part of these difficulties, promoting the improvement of their logistic activities, bigger facilities to access credits, advice in the business management and the extension of the profits. Providing therefore, an alternative way to the small and medium businessman that face the retailer concentration dominated by the big networks. Through the formation of the associativist netwoks, there is a chance that the small and medium companies become quicker, more flexible, and more competitive.